New methods to measure the built environment for human-scale travel research: Individual access corridor (IAC) analytics to better understand sustainable active travel choices - Bruce Appleyard (Journal of Transport and Land Use)
While travel is an inherently linear activity, most studies rely on coarse zonal measures of the built environment, likely missing key details important to human-scale travelers (pedestrians and bicyclists). To more fully understand these relationships, this study tests a new, linear spatial unit of analysis (the individual access corridor) in combination with finer-grained geospatial data (parcel, point, street network)—in sum, human-scaled measures for human-scale travel research.